Analysis of variations in the number of layers of hardfacing overlay ABREX 500 material on hardness,impact strength and microstructure with the SMAW process - Amri, Moh. Syaiful; Anggara, Dika; rohmat, Imam Khoirul; Kurniyanto, Hendri Budi; Pradana, Dika Septya (Journal of Welding Technology, 2023)
Hardfacing is a welding technique that functions to increase the surface hardness value of a material. Generally, hardfacing is done on low-carbon steel materials because low-carbon steel cannot be increased in hardness by heat treatment. For this reason, research will be carried out on the multilayer hardfacing process with the aim of obtaining optimal layer hardness. The methodology in this research is that multilayer hardfacing welding will be carried out consisting of 3 layers, 4 layers, and 5 layers, and each specimen has 2 buffer layer layers with E 309 electrodes for the hardfacing layer using HV 600 electrodes. This research reveals the influence of the number of layers of hardfacing on the hardness and toughness values. ABREX 500 material with a size of 150x150x10 mm was welded using the SMAW process using a current of 130 A. In this research, hardness and toughness tests were carried out. On test results. The base metal microstructure is dominated by a tempered martensite structure with a small amount of bainite and pearlite. In the structural area of the support layer, austenite and vermicular ferrite dominate. In the hardfacing layer area, austenite and vermicular ferrite, which are in dendritic form, dominate. The increase in hardness will occur significantly after hardfacing is carried out on the base metal. In a specimen, the more layers of hardfacing are added, the harder the material will be. The hardness of the specimen in 5 layers gets the most optimal value (higher) when compared with the hardness in 3 layers and 4 layers. In the 5-layer specimen, the resulting hardness value was 482.13 kgf/mm2, for the 4-layer specimen, the average value was 464.83 kgf/mm2, and in the 3-layer specimen, the hardness value was 444.13 kgf/mm2. For toughness testing, the highest toughness value was obtained, namely 1.32 (J/mm2) for the 3 layers specimen, compared to 4 layers with a toughness value of 1.25 (J/mm2) and 5 layer with a toughness value of 1.19 (J/mm2). The toughness value decreases as the hardness value increases.